Artikel Review: Teknologi Penangkapan Karbon Dioksida (CO2 Capture) Berbasis Membran - Material, Mekanisme, dan Tantangan Performa - Hasrul Hasrul; Arya Wiranata; Trisuciati Syahwardini (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Rising CO₂ emissions from industrial sectors drive the development of efficient and flexible carbon capture technologies. This review discusses membrane-based CO₂ capture with emphasis on membrane materials, transport mechanisms, and performance challenges under realistic operating conditions. The literature shows that polymer membranes, facilitated transport membranes, mixed matrix membranes, carbon molecular sieve membranes, and porous inorganic membranes each offer distinct advantages and limitations in permeability, selectivity, stability, and cost. Key challenges include low CO₂ partial pressure in post-combustion capture, the effects of moisture and contaminants, and material degradation such as plasticization and physical aging. Further progress requires material innovation, process optimization, and economic assessment to improve stability, efficiency, and industrial competitiveness in low-carbon applications